Translating transcendence in interior design a case study on the dignity of elderly residents through the analysis of social spaces in selected nursing homes - Padernal,Trisha Anne M.
This descriptive qualitative case study was conducted to explore the transcendence qualities of interior space that contribute to the dignity of the elderly. The study specifically aimed to identify the indicators of elderly resident's dignity, determine the physical properties of the social space in the nursing home, determine the activity patterns of the elderly in relation to the interior space, and analyze the physical properties and psychological impression of the space that contribute to the transcendence of the elderly. Three nursing homes were purposively selected. Interview participants were the owners, nurses, and caregivers. The social spaces observed were the living-dining areas and a garden. Data were gathered through a sequential multi method procedure - in-depth interviews, documentation through photographs and the production of a floor plan, activity mapping and interior space analysis instrument. Results show that indicators of dignity were spaces that were safe, clean and restful moments of interaction as well as solitude ; weekly fellowship, rosary praying and Bible reading. The nursing homes had either an open layout multi-use space or a garden for the social hall. Through the activity mapping, it was gathered that the elderly's most frequently observed activities were those classified as circulation activities. Results of the activity mapping were useful in developing design solutions to promote the elderly transcendence development such as social interaction, period of quiet solitude and sense of belonging. The results of the study may guide interior designers in the planning and implementation of guidelines and standards for the interior design of nursing homes in the Philippines. Further in-depth studies with bigger sample size and more nursing home participants regarding specific domains of transcendence are highly recommended.